Investigating the design practice in mobile health application development process to employ stakeholders’ creativity - Yu, Xinxin; Ramli, Saiful Hasley; Norowi, Noris Mohad; Surip, Siti Suhaily (Human Resources Management Academic Research Society (HRMARS), 2023)
Stakeholders struggle to communicate with designers about mobile health app design. Thus, mHealth apps must be developed using a conceptual framework to engage stakeholders' co-creation and inventiveness. This study aims to (1) identify design difficulties in mHealth apps, (2) assess the optimal strategy for creating a mobile health app for pregnant women, and (3) evaluate a co-creation design that harnesses stakeholders' creativity. A systematic literature review synthesis involved 70 papers. Analyzing existing literature during early research conceptualization helps develop a theoretical framework. Visualization health records for pregnant women, mHealth app evidence-based information conceptual frameworks, and necessary visualization were significant findings. Final pregnant women health visualization conceptual framework. This study proposes mHealth app design using evidence-based graphical data records for pregnant women to engage expert co-creativity. It encourages designers to use storyboarding to collaborate with stakeholders on mHealth app creation. Finally, this study suggests storyboarding for pregnant women's mHealth apps. Research is needed on storyboarding design methods for mHealth apps for pregnant women that employ experts' co-creativity.